2015
DOI: 10.1177/1352458514559298
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parental multiple sclerosis on early childhood development: A retrospective cohort study

Abstract: Background: Exposure to parental chronic illness is associated with several adverse developmental outcomes. Objectives: We examined the association between parental multiple sclerosis (MS) and childhood developmental outcomes. Methods: We conducted a population-based retrospective cohort study in Manitoba, Canada, using linked databases. The outcome was childhood development at 5 years of age, expressed as vulnerability (absent vs. present) on the Early Development Instrument (EDI). Logistic regression was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 32 publications
(56 reference statements)
2
22
0
1
Order By: Relevance
“…Several studies indicate parental mental health, emotional distress, and expressed emotions are more important determinants for the impact of MS on their offspring's psychosocial development (Bogosian et al, ; Razaz et al, ; Razaz, Joseph, et al, ) than the severity and type of MS. Therefore, the lack of information on mental health problems of the mother is a limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicate parental mental health, emotional distress, and expressed emotions are more important determinants for the impact of MS on their offspring's psychosocial development (Bogosian et al, ; Razaz et al, ; Razaz, Joseph, et al, ) than the severity and type of MS. Therefore, the lack of information on mental health problems of the mother is a limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using the strengths and difficulties questionnaire (SDQ) to measure psychosocial development confirms the association between mental health problems of parents with MS and increased internalizing and externalizing symptoms affecting their children (Bogosian, Hadwin, Hankins, & Moss‐Morris, ). Other studies find no adverse association of parental MS with children's development outcomes (Razaz et al, ) and no difference in overall difficulties between children of parents with MS and the general community (Steck et al, ), and some studies have shown an increase in prosocial behavior (Pakenham & Cox, ) and an increased feeling of being more empathic and grown‐up than peers (Bogosian, Moss‐Morris, Bishop, & Hadwin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that women with MS may have higher risk for delivering neonates with lower birth weight compared with healthy women [15][16][17] . Thus far no long-term adverse pediatric outcomes have been reported 18,19 .…”
Section: Fetal Developmentmentioning
confidence: 99%
“…Consequently, children of a parent with MS have demonstrated greater levels of distress, behavioural problems, and negative psychosocial behaviour compared with children of parents without MS . On the other hand, some studies have reported that children of a parent with MS and children of parents without MS do not differ on adjustment and developmental outcomes, except for adverse peer relationship issues …”
mentioning
confidence: 99%
“…Depression and anxiety affect individuals with MS at more than twice the frequency observed among people without MS . Chronic exposure to maternal depressive symptoms has been consistently shown to have an adverse effect on children's mental health . Given the high prevalence of mental health co‐morbidity among people with MS, it is possible that parental mental health mediates the relationship between parental MS and mental health outcomes in their children.…”
mentioning
confidence: 99%